Silage Formulation Based on Tithonia diversifolia and Panicum maximum: In Vitro Fermentation Evaluation for Tropical Feeding Systems - Dwi Ananta; Nadia Rahma; Fadilla Meidita; Yudha Endra Pratama (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Ensuring year-round availability of high-quality forage is critical for improving the productivity of ruminant livestock, particularly under tropical climatic conditions where seasonal fluctuations frequently disrupt feed supply. This study evaluated the fermentative quality of silage produced from varying ratios of Tithonia diversifolia and Panicum maximum using an in vitro rumen fermentation system. A Completely Randomized Design (CRD) was applied with five treatment groups (T0 = 0% Tithonia, T1 = 25%, T2 = 50%, T3 = 75%, and T4 = 100%) and three replicates each. After a 21-day ensiling period, samples were assessed for pH, total gas production, ammonia nitrogen (NH₃-N), and volatile fatty acids (VFA) using fresh rumen fluid from slaughtered cattle as the inoculum. Results revealed that increasing the proportion of T. diversifolia enhanced fermentative activity, as indicated by higher total gas and VFA production, and lower pH values. Treatment T3 (75% Tithonia) showed the most favorable fermentative profile, with significantly higher gas and VFA yields and NH₃-N concentrations within the optimal range for microbial protein synthesis. Conversely, T4 (100% Tithonia) exhibited signs of fermentative inhibition, likely due to anti-nutritional factors such as tannins and saponins. In contrast, T0 (100% Panicum) demonstrated limited fermentability due to its high fiber and low soluble carbohydrate content. These findings suggest that a 75:25 ratio of Tithonia diversifolia to Panicum maximum optimizes rumen fermentation and may serve as a promising strategy for improving silage quality in tropical forage systems.